THE IMPORTANCE OF LEARNING, TEACHING AND THE STUDY OF LAW - Jhon Cristyan Hancco Aguilar (2020)
This article focuses on establishing the importance that every law academic should know; be it as a student, university teacher, trial lawyer, judge, prosecutor and all connoissurs of the legal world; both in initial learning, also encompassing higher education and the continuouns stady of Law; The topics developed below were  considered in order to improve the quality of the teaching, stady and learning process of the future lawyer and the lawyer himself. Therefore, this article, through the stady and interpretation of the subject, begins to develop conceptualizing each of the relevant aspects of learning, teaching and the stady of law; citing authors such as Atienza, Carbonell, Ossorio, López; among others who develop  relevant issuues regarding Law.